Molecular dynamics study on the nano-void growth in face-centered cubic single crystal copper - Zhao, K.J.; Chen, C.Q.; Shen, Y.P.; Lu, T.J. (Computational materials science, 2009)
Cylindrical nano-void growth in face-centered cubic single crystal copper is studied by mean of molecular dynamics with the Embedded Atom Method. The problem is modeled by a periodic unit cell containing a centered nano-sized cylindrical hole subject to uniaxial tension. The effects of the cell size, crystalline orientation, and initial void volume fraction on the macroscopic stress–strain curve, incipient yield strength, and macroscopic effective Young’s modulus are quantified. Defect evolution in terms of dislocation emission immediately after incipient yielding is also investigated. Obtained results show that, for a given void volume fraction, cell size has apparent effects on the incipient yield strength but negligible effects on the macroscopic effective Young’s modulus. Moreover, the macroscopic effective Young’s modulus and incipient yield strength of the [ 1 ¯ 1 0]–[1 1 1]–[1 1 2 ¯ ] orientated system are found to be much more sensitive to the presence of void than those of the [1 0 0]–[0 1 0]–[0 0 1] system.